Dysregulation of REST and its target genes impacts the fate of neural progenitor cells in down syndrome - Tan, Huang; Fakurazi, Sharida; Cheah, Pike-See; Ling, King-Hwa (Nature Research, 2025)
Increasing shreds of evidence suggest that neurogenic-to-gliogenic shift may be critical to the abnormal neurodevelopment observed in individuals with Down syndrome (DS). REST, the Repressor Element-1 Silencing Transcription factor, regulates the differentiation and development of neural cells. Downregulation of REST may lead to defects in post-differentiation neuronal morphology in the brain of the DS fetal. This study aims to elucidate the role of REST in DS-derived NPCs using bioinformatics analyses and laboratory validations. We identified and validated vital REST-targeted DEGs: CD44, TGFB1, FN1, ITGB1, and COL1A1. Interestingly, these genes are involved in neurogenesis and gliogenesis in DS-derived NPCs. Furthermore, we identified nuclear REST loss and the neuroblast marker, DCX, was downregulated in DS human trisomic induced pluripotent stem cells (hiPSCs)-derived NPCs, whereas the glioblast marker, NFIA, was upregulated. Our findings indicate that the loss of REST is critical in the neurogenic-to-gliogenic shift observed in DS-derived NPCs. REST and its target genes may collectively regulate the NPC phenotype.